Aneurysm of Anterior Inferior Cerebellar Artery-posterior Inferior Cerebellar Artery Variant - Ansari, Khursheed Ahmad (Asian J Neurosurg, 2018)
Aneurysms arising from anterior inferior cerebellar artery-posterior inferior cerebellar artery (AICA-PICA) variant are extremely rare. They usually present with subarachnoid hemorrhage. This is probably the second case report of a large thrombosed AICA-PICA variant aneurysm presenting as a cerebellopontine angle mass lesion with cranial nerve palsy, managed successfully by surgical clipping.